2006
DOI: 10.1055/s-2006-946676
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Quinones from Teak (Tectona grandis) on Fungal Cell Wall Stress

Abstract: Teak ( Tectona grandis L.f., Verbenaceae) sawdust extract inhibited the growth of Aspergillus niger. Centrifugal partition chromatography was used to isolate the active compounds. By (1)H-NMR the active compounds were identified as deoxylapachol and tectoquinone. Two A. niger transgenic strains which show induction of 1,3 -alpha-D-glucan synthase were used as a cell wall damage model. The result showed that deoxylapachol from T. grandis extract induced fungal cell wall stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 4 publications
1
21
0
1
Order By: Relevance
“…Haupt et al (2003) that the quantity of tectoquinone and its ratio to desoxylapachol appears to be a good indicator of antifungal properties, while Thulasidas and Bhat (2007) observed that naphtaquinone is the single major compound which determines the decay resistance of teak. Sumthong (2006) found that both tectoquinone and desoxylapachol are active compounds against Aspergillus niger. These findings confirmed the presence of toxic components in the sapwood and heartwood of young trees.…”
Section: Relationship Between Extractive Compounds and Total Extractimentioning
confidence: 98%
See 1 more Smart Citation
“…Haupt et al (2003) that the quantity of tectoquinone and its ratio to desoxylapachol appears to be a good indicator of antifungal properties, while Thulasidas and Bhat (2007) observed that naphtaquinone is the single major compound which determines the decay resistance of teak. Sumthong (2006) found that both tectoquinone and desoxylapachol are active compounds against Aspergillus niger. These findings confirmed the presence of toxic components in the sapwood and heartwood of young trees.…”
Section: Relationship Between Extractive Compounds and Total Extractimentioning
confidence: 98%
“…Yamamoto et al (1998) demonstrated the significant effects of teak wood extractives on wood-destroying fungi. Quinones and their derivatives have been reported to act against termite and fungal attacks (Haupt et al, 2003;Rudman and Gay, 1961;Sandermann and Simatupang, 1966;Sumthong et al, 2006;Thulasidas and Bhat, 2007). Differences in natural durability may be related to the concentration of toxic extractable substances of wood accumulation during the formation of heartwood.…”
Section: Introductionmentioning
confidence: 99%
“…Natural durability is undoubtedly derived from the wood's extractives. Quinones and their derivatives have been reported to act against termite and fungal attacks (Rudman and Gay 1961;Sandermann and Simatupang 1966;Haupt et al 2003;Sumthong et al 2006;Thulasidas and Bhat 2007). Windeisen et al (2003) detected some terpenes and toxic quinones in teakwood by petroleum ether and acetone in successive extractions.…”
Section: Extractive Contentsmentioning
confidence: 99%
“…Several studies concerning the effect of the extractives content on the natural durability of teak have been published (Rudman et al 1967, Lukmandaru et al 2015. Quinones and their derivatives in the extractives of teak have been reported to defend against termite and fungal attack (Sumthong et al 2006;Thulasidas et al 2007;Niamké 2011). The high decay resistance of teak heartwood is postulated to be due to a synergistic effect of the decay active ethanol extracts and caoutchouc (Sandermann 1964;Yamamoto et al 1998).…”
Section: Introductionmentioning
confidence: 99%